Farmed blue mussels (Mytilus edulis)—a nutrient-dense resource retaining nutritional value through processing - Bjerknes, Hanne; Elvevoll, Edel O.; Alterskjær Sundset, Monica; Langdal, Andreas; Eilertsen, Karl-Erik (Frontiers in Nutrition, 2024)
This study investigated how farmed blue mussels (Mytilus edulis) can optimize human nutrient intake. A particular focus was on assessing nutrient preservation during steaming and freeze-drying, processes that could deplete nutrients. The study compared the content of essential amino acids and fatty acids in steamed and freeze-dried blue mussels to the nutritional needs of humans and farmed Atlantic salmon (Salmo salar). Additionally, it assessed the ethyl acetate method versus the traditional, more toxic Folch method for lipid extraction from blue mussels. Both steaming and freeze-drying effectively preserved essential amino acids and fatty acids in blue mussels. A 100 g serving of steamed blue mussels contributes from 26.8 ± 0.78% (Phe) to 54.9 ± 1.66% (Thr) of the daily recommended intake of essential amino acids (EAA). For steamed freeze-dried blue mussels, over 100% of the recommended intake is met for all EAA and as much as 243% for threonine. The 100 g serving will also provide 271 mg eicosapentaenoic acid (EPA; 20:5n-3) and 220 mg docosahexaenoic acid (DHA; 22:6n-3), thus covering the required intake of n-3 long-chain polyunsaturated fatty acids for adults as well as the recommended intake for pregnant and lactating women. Mussels are non-fed filter feeders that generally provide these nutrients with significantly lower environmental footprints, measured as global warming, eutrophication, and acidification, compared to farmed Atlantic salmon. Blue mussels can also be a valuable feed ingredient for farmed Atlantic salmon. Finally, it was demonstrated that the ethyl acetate method is not suited for lipid extraction from blue mussels, as the lipid yield was only half compared to the lipid yield using the Folch method.